2022
DOI: 10.1002/advs.202105586
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes‐Loaded Electroconductive Hydrogel Synergistically Promotes Tissue Repair after Spinal Cord Injury via Immunoregulation and Enhancement of Myelinated Axon Growth

Abstract: Electroconductive hydrogels are very attractive candidates for accelerated spinal cord injury (SCI) repair because they match the electrical and mechanical properties of neural tissue. However, electroconductive hydrogel implantation can potentially aggravate inflammation, and hinder its repair efficacy. Bone marrow stem cell‐derived exosomes (BMSC‐exosomes) have shown immunomodulatory and tissue regeneration effects, therefore, neural tissue‐like electroconductive hydrogels loaded with BMSC‐exosomes are devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 61 publications
4
168
0
Order By: Relevance
“…In brief, it turned out that GMN group effectively promoted the connection between the newborn nerves with the injured nerve. Lei et al has proved that the electroconductive hydrogel with bone marrow stem cell-derived exosomes can improve the microenvironment of the injured site [ 41 ]. It showed that electroconductive hydrogel also need the good biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, it turned out that GMN group effectively promoted the connection between the newborn nerves with the injured nerve. Lei et al has proved that the electroconductive hydrogel with bone marrow stem cell-derived exosomes can improve the microenvironment of the injured site [ 41 ]. It showed that electroconductive hydrogel also need the good biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…BMSCs (BMSCs-Exos). BMSCs were collected by fushing the bone marrow cavity of 2-week-old rats' tibia and femur, as previously described [19]. Te isolated BMSCs were put in a low-glucose DMEM (Gibco) mixture containing 10% serum and cultured at 37 °C with 5% CO 2 in a cell culture incubator.…”
Section: Isolation Identifcation and Staining Of Exosomes Frommentioning
confidence: 99%
“…The larger the radius, the larger the charge transfer resistance. 70 The introduction of Cu 2+ and PANI enhanced the conductivity of hydrogels.…”
Section: Resultsmentioning
confidence: 99%